2011
DOI: 10.1055/s-0031-1300097
|View full text |Cite
|
Sign up to set email alerts
|

General Pharmacological Properties of YJA20379-8, a New H+/K+-ATPase Inhibitor with Anti-ulcer Activities

Abstract: The general pharmacological properties of YJA20379-8 (3-butyryl-4-[(R)-1-methylbenzylamino]-8-ethoxy-1,7-naphthyridine, CAS 187654-40-6), a new H+/K(+)-ATPase inhibitor with anti-ulcer activities, were investigated in mice, rats and guinea pigs. YJA20379-8 at oral doses of 25, 50 and 100 mg/kg did not affect the locomotor activity, hexobarbital hypnosis and motor coordination in mice. The drug did not have analgesic action and anticonvulsant action at the doses of 100 mg/kg p.o. The respiration and blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…According to the previous study, in the restoration of the back surface field (BSF) type cell, which is an early model of the crystalline silicon solar cell, almost no decrease in output due to cell deterioration was observed. [ 30 ] The cell taken for this experiment was of passivated emitter rear contact (PERC) type, which was the next generation of BSF cells, and in this case, it was found that the higher the initial efficiency, the higher the degradation rate of the cell when the module is restored. The decrease in output was mainly caused by a decrease in V mp , which can be found in the increase of series resistance elements due to cell deterioration.…”
Section: Resultsmentioning
confidence: 99%
“…According to the previous study, in the restoration of the back surface field (BSF) type cell, which is an early model of the crystalline silicon solar cell, almost no decrease in output due to cell deterioration was observed. [ 30 ] The cell taken for this experiment was of passivated emitter rear contact (PERC) type, which was the next generation of BSF cells, and in this case, it was found that the higher the initial efficiency, the higher the degradation rate of the cell when the module is restored. The decrease in output was mainly caused by a decrease in V mp , which can be found in the increase of series resistance elements due to cell deterioration.…”
Section: Resultsmentioning
confidence: 99%